A nationwide survey of public healthcare providers’ impressions of family medicine specialists in Malaysia: a qualitative analysis of written comments - Boon How Chew; Ai Theng Cheong; Mastura Ismail; Zuhra Hamzah; Mazapuspavina Md Yasin; Norsiah Ali; Noridah Mohd-Salleh; Baizury Bashah; Mohd Radzniwan A Rashid (BMJ Publishing Group, 2024)
Objective To examine the expectation of public healthcare providers/professionals (PHCPs) who are working closely with family medicine specialists (FMSs) at public health clinics.